PENGARUH MOTIVASI KERJA TERHADAP KEPUASAN KERJA: META ANALYSIS - Silviawati, Silviawati; Novriadi, Asep; Zaitul, Zaitul; Yunas, Yosfan (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Job satisfaction is a key factor determining employee productivity and retention in an organization, and work motivation is believed to be one of its main predictors. This meta-analysis study aims to determine the extent of work motivation’s influence on employee job satisfaction and how work motivation significantly influences employee job satisfaction. Articles were collected using academic databases such as Google Scholar, Garuda, and SINTA with keywords such as work motivation, job satisfaction, and employees. The data obtained were analyzed by calculating the effect size of each journal. The random-effects model shows that work motivation has a significant effect on employee job satisfaction with a value of 0,083; p < 0,001 in the small category. This indicates that work motivation can consistently increase job satisfaction across various organizational contexts. Increasing work motivation is an important strategy for management to create a positive and productive work environment.